Enterprise Architecture Dimension eGovernment Ranking Indonesia - Lestari, Sri; Mardiana, Siti; Rijayana, Iwan; Murnawan; Virgana, RAE; Samihardjo, Rosalin; Nugraha, Ucu (International Journal of Psychosocial Rehabilitation, 2020)
Republic of Indonesia, under Presidential Instruction No. 3 of 2003 on National Policy and Strategy Development of e-Government, any government agency should have a Strategic Plan for Development of e-Government. XYZ City government plan that the master plan development of information and communication technology is the basis for the development of applications and information technology infrastructure in the city government XYZ. This study uses the dimensions of e-Government ranking of Indonesia (EGRI) that the guidelines created by the Ministry of Communication and Information of the Republic of Indonesia have defined five dimensions of the ICT master plan that will be reviewed, namely Policies, Institutions, Infrastructure, Application, and Planning.